2015
DOI: 10.1371/journal.pone.0139442
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Community-Based Physical Activity Program KM2H2 for Stroke and Heart Attack Prevention among Senior Hypertensive Patients: A Cluster Randomized Controlled Phase-II Trial

Abstract: ObjectiveTo evaluate the efficacy of the program Keep Moving toward Healthy Heart and Healthy Brain (KM2H2) in encouraging physical activities for the prevention of heart attack and stroke among hypertensive patients enrolled in the Community-Based Hypertension Control Program (CBHCP).DesignCluster randomized controlled trial with three waves of longitudinal assessments at baseline, 3 and 6 months post intervention.SettingCommunity-based and patient-centered self-care for behavioral intervention in urban setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 39 publications
(60 reference statements)
3
54
0
1
Order By: Relevance
“…*Primary outcome indicates whether authors identified change in physical activity as a primary or secondary outcome of the study.†Value for total sample; includes women in mixed-sex studies (ie, Gong et al 48, 2015 (42% men), Werkman et al 67, 2010 (85% men)).‡England, Norway, Netherlands and Portugal.Cluster, cluster randomised trial; MetS, metabolic syndrome; Obj, objective; PA, physical activity; RCT, randomised controlled trial; Sub, subjective.…”
Section: Resultsmentioning
confidence: 99%
“…*Primary outcome indicates whether authors identified change in physical activity as a primary or secondary outcome of the study.†Value for total sample; includes women in mixed-sex studies (ie, Gong et al 48, 2015 (42% men), Werkman et al 67, 2010 (85% men)).‡England, Norway, Netherlands and Portugal.Cluster, cluster randomised trial; MetS, metabolic syndrome; Obj, objective; PA, physical activity; RCT, randomised controlled trial; Sub, subjective.…”
Section: Resultsmentioning
confidence: 99%
“…The KM2H 2 is a behavioral intervention that, guided by the SC theory, motivates physical activity by increasing access to the social and emotional resources. A recent study shed a light on its effectiveness for use in community settings (Gong, Chen, & Li, 2015).…”
Section: So Cial C Apital and Neurolog Ic Al Conditionsmentioning
confidence: 99%
“…[9] The TTM has been applied in many health behaviour interventions, where it resulted in reduction in blood pressure, stroke and heart attack incidents among patients with hypertension. [10] TTM also enhanced medication adherence in patients with hypertension [11] and individuals receiving lipid lowering drugs. [12] The intervention first uses baseline information given by the individual, with an aim to alter self-efficacy, cues or other psychosocial factors using the following TTM principles: [13] (1) Precontemplation: Messages that demonstrate the advantages of following a healthy lifestyle are provided to patients enrolled in the study.…”
Section: Introductionmentioning
confidence: 96%